ANALISIS TANTANGAN HUKUM DALAM PENGEMBANGAN EKONOMI DIGITAL DAN E-COMMERCE DI ERA TEKNOLOGI MODERN: Analisis Tantangan Hukum Dalam Pengembangan Ekonomi Digital Dan E-Commerce Di Era Teknologi Modern - Nasarudin; Zuhrah (Program Studi Ekonomi Syariah, 2025)
The development of the digital economy and e-commerce in the era of modern technology faces significant legal challenges, regulatory gaps, consumer protection, and data security. The purpose of this study is to analyze the legal challenges in the development of the digital economy and e-commerce, identify regulatory gaps, create an adaptive and inclusive legal framework to support the growth of the digital economy in Indonesia. Qualitative research methods, the research approach uses a library research approach. The data collection method uses document review. The analysis used is content analysis. The results of the study indicate that the legal challenges in the development of the digital economy and e-commerce in the era of modern technology can be grouped into several main aspects, namely regulation, consumer protection, data security, and sustainability of the digital ecosystem. First, regulatory gaps are a significant problem because many laws are no longer relevant to the development of digital technology, such as cross-border trade and digital taxation. In addition, the lack of harmonization of laws between countries hinders international trade. Furthermore, consumer protection is also a concern, where many consumers face unclear rights and responsibilities in online transactions, as well as the risk of fraud and lack of transparency from service providers. On the other hand, data security and privacy are major issues, with regulations that are still weak in protecting personal information and low public awareness of the importance of data privacy. Challenges to the sustainability of the digital ecosystem also arise, especially related to the inequality of access to technology and the imbalance of power between large and small business actors. This study emphasizes the urgent need to develop regulations that are more adaptive and flexible to technological innovation, as well as the importance of collaboration between governments, industry players, and the international community to overcome global challenges in the digital economy.